Pengaruh Metode Role Playing terhadap Prestasi Belajar Peserta Didik pada Mata Pelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiah - Hasyim, Hasyim; Mauliana, Nia Siska (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
Using appropriate and effective learning methods is one of the factors that determine the success of the teaching and learning process. The purpose of this study is to describe the application of the Role Playing method in SK subjects, to identify student achievement in Islamic Cultural History subjects, and to measure the effect of the application of the Role Playing method on student achievement in SKI subjects. This research is a quantitative correlative type. The results of this study indicate that the percentage of the Role playing method in the Islamic Cultural History subject at MI Azhariyah Tegalrejo for the 2021/2022 academic year is 91%, which indicates very well. The level of learning achievement of students in the Islamic Cultural History subject is 76.67%, indicating good. The Role Playing method has a strong influence on student achievement in SKI subjects at Madrasah Ibtidaiyah.